Diagnostic magnetic resonance imaging characteristics of congenital mesoblastic nephroma: a retrospective multi-center International Society of Pediatric Oncology-Renal Tumor Study Group (SIOP-RTSG) radiology panel study - Beek, Justine van de; Schenk, Jens-Peter; Morosi, Carlo; Watson, Tom A.; Coma, Ana; Graf, Norbert; Chowdhury, Tanzina; Ramírez-Villar, Gema L.; Spreafico, Filippo; Welter, Nils; Dzhuma, Kristina; van Tinteren, Harm; et al. (Pediatric radiology, 2024)
Congenital mesoblastic nephroma is the most common solid renal tumor in neonates. Therefore, patients <3 months of age are advised to undergo upfront nephrectomy, whereas invasive procedures at diagnosis in patients ≥3 months of age are discouraged by the International Society of Pediatric Oncology-Renal Tumor Study Group (SIOP-RTSG). Nevertheless, discriminating congenital mesoblastic nephroma, especially from the more common Wilms tumor, solely based on imaging remains difficult. Recently, magnetic resonance imaging (MRI) has become the preferred modality. Studies focusing on MRI characteristics of congenital mesoblastic nephroma are limited.